New records of snipe eels (Anguilliformes: Nemichthyidae) from the Pacific coast of lower Central America - Cruz Mena, Óscar Isaac (2016)
Background: New records of occurrence of two snipe eels (Avocettina bowersii and Nemichthys scolopaceus), poorly known for the Pacific coast of Costa Rica and Panama are herein reported. Results: Specimens, 45 in total (28 and 17, respectively), were collected between 1972 and 1973 at depths between 295 and 1000 m. Descriptions based on specimens as well as comparative morphometric and distributional information by species are herein presented and discussed. A key to the identification of the eastern Pacific species of the family also is presented. Conclusion: These findings increase the knowledge on the Central American marine ichthyofauna and provide evidence of a broader distributional pattern for these species in the eastern Pacific region.